2016
DOI: 10.1016/j.cmet.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Biogenesis and Proteome Remodeling Promote One-Carbon Metabolism for T Cell Activation

Abstract: Summary Naïve T cell stimulation activates anabolic metabolism to fuel the transition from quiescence to growth and proliferation. Here we show that naïve CD4+ T cell activation induces a unique program of mitochondrial biogenesis and remodeling. Using mass spectrometry, we quantified protein dynamics during T cell activation. We identified substantial remodeling of the mitochondrial proteome over the first 24 hr of T cell activation to generate mitochondria with a distinct metabolic signature, with one carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
294
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(306 citation statements)
references
References 41 publications
10
294
0
2
Order By: Relevance
“…We therefore analyzed mitochondrial shape in T cells at different times after activation ± αCD28. T cells primed (+) αCD28 displayed elongated mitochondria early after activation (Buck et al, 2016; Ron-Harel et al, 2016), whereas T cells primed (−) αCD28 had more spherical mitochondria (Figures 2A and S2A–B). Spherical mitochondria are associated with rapidly dividing glycolytic T cells (Buck et al, 2016), a phenotype observed in mature IL-2 T E cells primed ± αCD28 (Figures 2A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore analyzed mitochondrial shape in T cells at different times after activation ± αCD28. T cells primed (+) αCD28 displayed elongated mitochondria early after activation (Buck et al, 2016; Ron-Harel et al, 2016), whereas T cells primed (−) αCD28 had more spherical mitochondria (Figures 2A and S2A–B). Spherical mitochondria are associated with rapidly dividing glycolytic T cells (Buck et al, 2016), a phenotype observed in mature IL-2 T E cells primed ± αCD28 (Figures 2A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…This is met by large changes in gene expression that serve both to mobilize existing stored 1C from 5-formyl-THF by 5-formyltetrahydrofolate cycloligase, and to produce new 1C units from serine via the SHMT2-MTHFD2 pathway (Ron-Harel et al, 2016). Interestingly, inhibition of T cell activation by SHMT2 short hairpin RNA (shRNA) was fully rescued by a combination of formate and the general antioxidant N-acetylcysteine, but not either alone, implicating the mitochondrial 1C pathway in T cells in both 1C unit generation and redox defense, as previously observed in HEK293T cells (Ducker et al, 2016).…”
Section: C Metabolism In Development and Proliferative Adult Tissuesmentioning
confidence: 99%
“…These results suggest that K280 can be a potential cancer therapy site. SHMT2 is a universal enzyme for cell proliferation and T-cell activation (44). A specific single amino acid mutation technique changing K 280 to E can be used for suppression of SHMT2-related cancer, providing a potential simple tool for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%